Bankruptcy Costs and the New Bankruptcy Code - WARNER, JEROLD B.; WHITE, MICHELLE J. (Journal of Finance, 1983)
BANKRUPTCY COSTS are the deadweight economic costs of firms going bankrupt. They include both ex post bankruptcy costs incurred after a firm's bankruptcy filing, such as transactions costs, and ex ante bankruptcy costs incurred before the filing, such as those resulting from creditors' attempts to reduce their losses if bankruptcy occurs and/or managers' attempts to raise the expected return to equity by increasing the firm's risk.1 This paper has two purposes. First it proposes a model of bankruptcy costs which focuses on the costs of inefficient decision making before the firm's actual bankruptcy filing. The model implies upper bound expressions for total bankruptcy costs. Second, the new U.S. Bankruptcy Code2 went into effect late in 1979 and made important changes in bankruptcy reorganization procedures. The paper poses the question of whether the changes made under the new Code tend to raise or lower aggregate U.S. bankruptcy costs. We approach this question by calculating the upper bound expressions suggested by the model, using parameter values from both before and after the new Code took effect.